2023
DOI: 10.1021/acsami.3c07838
|View full text |Cite
|
Sign up to set email alerts
|

Reversible and Turn-On Fluorescence Detection of Phosphate in Aqueous Solution and Living Cell Imaging by Supramolecular Metallacycles with AIE-Active Ligands

Ya-Lan Kou,
Jin Tong,
Cong Meng
et al.

Abstract: Luminescent supramolecular metallacycles have attracted great interest as a new promising class of sensing substrates. In this work, two tetraphenylethene (TPE)-based diimidazole and dipyrazole ligands with the aggregation-induced emission (AIE) feature were designed for the construction of supramolecular tetragonal metallacycles 1–4 with two 90° mononuclear [(bpy)M]2+ or dinuclear [(bpy)2M2]4+ acceptors (bpy = 2,2′-dipyridine; M = Pd, Pt), in which the fluorescence can be quenched to an “off” state due to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Literature reports revealed that various types of promotors have been used in order to induce the self-assembly of organic-organic nanohybrids. [13][14][15][16][17][18][19][20][21][22][23] In particular extensive research has been carried out on anion induced selfassemblies of the peptide-based materials. Therefore, keeping in mind the importance of anions as promotors, we have analysed the effect of anions on fluorescence profiles of developed nanohybrids.…”
Section: Morphological Studies Of Nanohybridsmentioning
confidence: 99%
See 2 more Smart Citations
“…Literature reports revealed that various types of promotors have been used in order to induce the self-assembly of organic-organic nanohybrids. [13][14][15][16][17][18][19][20][21][22][23] In particular extensive research has been carried out on anion induced selfassemblies of the peptide-based materials. Therefore, keeping in mind the importance of anions as promotors, we have analysed the effect of anions on fluorescence profiles of developed nanohybrids.…”
Section: Morphological Studies Of Nanohybridsmentioning
confidence: 99%
“…This AIEE mechanism has potential applications in chemical sensing, photonic devices, bio-sensing, bio-imaging and light harvesting. 20–22…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation